2019
DOI: 10.1128/mbio.00300-19
|View full text |Cite
|
Sign up to set email alerts
|

Unique, Diverged, and Conserved Mitochondrial Functions Influencing Candida albicans Respiration

Abstract: Candida albicans is an opportunistic fungal pathogen of major clinical concern. The virulence of this pathogen is intimately intertwined with its metabolism. Mitochondria, which have a central metabolic role, have undergone many lineage-specific adaptations in association with their eukaryotic host. A screen for lineage-specific genes identified seven such genes specific to the CTG clade of fungi, of which C. albicans is a member. Each is required for respiratory growth and is integral to expression of complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 92 publications
(161 reference statements)
1
61
0
Order By: Relevance
“…Recently, a study identified seven genes ( Nuo3 , Nuo4 , Nue1 , Nue2 , Qce1 , Coe1 , and Coe2 ) that are unique to the CTG fungal clade, which is so named because they generally translate CTG as serine rather than leucine. The CTG fungal clade contains multiple important human pathogens, including C. albicans , and showed that they are required for full mitochondrial respiratory metabolism and fungal virulence [ 13 ], implying that these clade-specific mitochondrial factors might represent novel antifungal therapeutic targets. The mitochondrial respiratory chain is composed of four large multi-subunit enzymes, complexes I to IV.…”
Section: Potential For Mitochondrial Factors As Novel Antifungal Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a study identified seven genes ( Nuo3 , Nuo4 , Nue1 , Nue2 , Qce1 , Coe1 , and Coe2 ) that are unique to the CTG fungal clade, which is so named because they generally translate CTG as serine rather than leucine. The CTG fungal clade contains multiple important human pathogens, including C. albicans , and showed that they are required for full mitochondrial respiratory metabolism and fungal virulence [ 13 ], implying that these clade-specific mitochondrial factors might represent novel antifungal therapeutic targets. The mitochondrial respiratory chain is composed of four large multi-subunit enzymes, complexes I to IV.…”
Section: Potential For Mitochondrial Factors As Novel Antifungal Tmentioning
confidence: 99%
“…Loss of these proteins can lead to deficiencies in respiration and virulence [ 21 , 72 ]. Similarly, deletion of Nue1 , Nue2 , Nuo3 , or Nuo4 can impair complex I function, causing deficiencies in respiration and virulence [ 13 ], making them attractive antifungal drug targets. Additionally, dysfunction of complex I can lead to ROS accumulation in mitochondria, which in turn promotes fungal cell death [ 76 ].…”
Section: Potential For Mitochondrial Factors As Novel Antifungal Tmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the integrity and function of mitochondria are essential to the virulence of C. albicans. Mutations affecting any one of a number of mitochondrial functions, including mitochondrial ribosome synthesis, mitochondrial transcription or genome maintenance, protein import, or functioning of the electron transport chain (ETC), result in C. albicans virulence defect (12,26,27,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that orf19.2500 mutant could not grow on alternative carbon sources indicated a respiratory defect likely due to a faulty electron transport chain (12). To test this hypothesis, we carried out Seahorse assays to test the respiratory prowess of the isolated mitochondria of the mutant strain, in the presence of Complex I (CI) substrates (pyruvate + malate) ( Fig 3B).…”
Section: Orf192500 Localizes To the Mitochondria And Plays A Key Rolmentioning
confidence: 99%